PENGGUNAAN MEDIA HANDPHONE DALAM PRESENTASI MAHASISWA DAN DAMPAKNYA TERHADAP PROSES PEMBELAJARAN DI KELAS IV D PGSD UNIVERSITAS NUSA CENDANA - Langko, Carolina; Mika, Febromergiani; Maria Euprasia Sasi; Merlin Benu; Nana Naysila Chintya Nahak; Gaudensius Jati Lamauran Koten; Hiwa Wonda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the use of mobile phones in student presentations and their impact on the learning process among fourth-semester students of the Elementary School Teacher Education Program (PGSD) at Universitas Nusa Cendana. The study employed a quantitative descriptive approach involving 33 students as respondents. Data were collected through classroom observations and questionnaires using a five-point Likert scale. The collected data were analyzed using PSPP software to determine the percentages and tendencies of respondents' answers. The findings indicate that the use of mobile phones in presentations has both positive and negative impacts on the learning process. The positive impact is reflected in the students' ability to access additional information and references quickly during presentations. A total of 90.9% of respondents stated that mobile phones helped them obtain additional information, with a mean score of 4.27, categorized as very high. However, the use of mobile phones also negatively affects student interaction and critical thinking skills. About 66.6% of respondents admitted that mobile phone use reduced interaction with the audience and influenced their critical thinking abilities. Furthermore, 75.7% of the students reported using Artificial Intelligence (AI) to help answer questions during presentations. This study concludes that mobile phones and AI can support the learning process when used wisely and proportionally. Therefore, appropriate regulations and digital literacy are needed to ensure that technology functions as a learning aid rather than replacing students' independent thinking processes.